EFFECT OF DUST DEPOSITION ON THE PERFORMANCE OF PHOTOVOLTAIC PANELS (Web of Technology: Multidimensional Research Journal, 2025)
Solar photovoltaic power plants are ideally located in regions with high levels of insolation. Photovoltaic performance is affected by high cell temperatures, contamination, mismatch and other losses associated with the balance of systems. It is critical to understand the implications of each of these losses on system performance. This paper attempts to understand the performance loss due to dust through a dynamic study of the IV performance of panels under different contamination conditions in an open-air experimental test rig. Additionally, this paper discusses the results of an indoor study simulating the performance of photovoltaic panels under different dust deposition regimes.